Trust to What? Business Theology in Pekalongan Batik Industry - Susminingsih (LP2M IAIN Pekalongan, 2017)
The research question are what the problematic antropological assmptions of businnes theory through batik industry, what the common theological approachses to establish the interplay between the theological construction which grow up as well as their businnes behavior. The type of this research is field research, with qualitative-descriptive approach. The result show that 1) the problematic anthropological assumptions of business theory through batik industry consist of social and cultural Enviroment dilemma and multimedimension business decisions : humanity, enviroment, and transcendence. 2) The commaon theological approaches to business are : human is a creature endowed with reason, human is a creature whose have fellings, and human ezistence is characterized by consciousness in behaving. 3) The Moslem batik business theologized in many ways : believe in self, believe in other, believe in the giver of destiny, God involved in business, humans have the right and obligatons to conserve the harmony of the universe.